2020
DOI: 10.1186/s40001-020-00431-4
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture pretreatment alleviates myocardial injury through regulating mitochondrial function

Abstract: Background: Electroacupuncture is well known for its advantageous neuroanalgesic and therapeutic effects on myocardial ischemia-reperfusion injury. The purpose of the present research was to verify whether electroacupuncture can alleviate bupivacaine-induced myocardial injury. Methods: Specific pathogen-free Wistar rats were used to establish the bupivacaine-induced myocardial injury model. Western blot, PCR, transmission electron microscope and enzyme-linked immunosorbent (ELISA) methods were used to evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In the presence of dysphagia caused by pharyngeal muscle involvement, gastrogavage and partial pharyngeal muscle dissection could be beneficial [ 23 ]. Other comprehensive treatments included ahigh-energy diet [ 24 ], aerobic endurance exercise [ 25 ] (except for those with fever, muscle pain, or in a hunger state), and physiotherapy [ 26 ]. Patients who underwent surgery should have intravenous sugar-containing fluids administered before anesthesia to avoid catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of dysphagia caused by pharyngeal muscle involvement, gastrogavage and partial pharyngeal muscle dissection could be beneficial [ 23 ]. Other comprehensive treatments included ahigh-energy diet [ 24 ], aerobic endurance exercise [ 25 ] (except for those with fever, muscle pain, or in a hunger state), and physiotherapy [ 26 ]. Patients who underwent surgery should have intravenous sugar-containing fluids administered before anesthesia to avoid catabolism.…”
Section: Resultsmentioning
confidence: 99%
“…According to the theory of “Xingnao Kaiqiao Acupuncture” in traditional Chinese medicine [ 15 ], three acupuncture points were selected as the target points: bilateral Neiguan [ 16 ] (PC6, on the palmar side of the forearm, 3 cm proximal to the transverse carpal crease, between the palmaris longus tendon and the radial flexor carpi tendon), Yintang [ 17 ] (GV29 ], on the forehead of the human body, between the two eyebrows) and bilateral Zusanli [ 18 ] (ST36, 3 inches below the outer knee). Patients in the TEAS group received perioperative TEAS by two experienced researchers and the treatment time was 30 min before the induction of anesthesia until the end of the surgery, 1 day before operation, and from the first day to the third day after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that EA pretreatment can reduce myocardial caspase-1 and IL-1β, inhibit the activation of NLRP3 inflammatory bodies, and play a protective role in the heart [95] . EA pretreatment can promote the synthesis of adenosine triphosphate (ATP), inhibit the expression of ROS, upregulate the level of anti-apoptotic protein Bcl-2, improve mitochondrial dysfunction, reduce cardiomyocyte apoptosis, and improve myocardial injury [96] . EA can also significantly inhibit the degree of ST-segment elevation, improve left ventricular dysfunction, and reduce systolic and diastolic blood pressure by reducing the release of cardiac norepinephrine [97] .…”
Section: Acupuncture Nervous System Symptoms Related To Covid-19mentioning
confidence: 99%